Emotion Processes in Knowledge Revision. Issue 5 (4th July 2017) - Trevors, Gregory J.; Kendeou, Panayiota; Butterfuss, Reese
ABSTRACT: In recent years, a number of insights have been gained into the cognitive processes that explain how individuals overcome misconceptions and revise their previously acquired incorrect knowledge. The current study complements this line of research by investigating the moment-by-moment emotion processes that occur during knowledge revision using a think-aloud methodology. Undergraduate students read both refutation and nonrefutation texts and reported out loud their thoughts, which were coded along valence and activation dimensions of emotions. Results showed that at key points during reading, emotions differed within and between experimental text conditions. Further, exploratory mediational analysis showed that surprise was an influential emotion for learning. Findings are discussed in terms of theoretical contributions to our basic understanding of the role of emotions during knowledge revision.